The effect of red light (660 nm) on proliferative activity and growth reactions in seedlings of plants with contrast photoperiodic reaction - Avksentieva, O.; Batueva, E. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2020)
The results of a study of the effect of red light irradiation (660 nm) on the proliferative activity of root meristems and growth reactions of plant seedlings with contrast photoperiodic reactions are presented in this paper. Plants of the family Fabaceae contrasting in the photoperiodic reaction were used as plant material: long-day plants (LDP) of peas (Pisum sativum L.) of the Metsenat variety and short-day plants (SDP) of soybean (Glycine max (L.) Merr.) of the Korsak variety. Phytochromes were activated by irradiating the aerial part of the experimental seedlings with monochromatic red light (RL) of 660 nm using an LED matrix for 30 minutes for 5 days. The proliferative activity of meristem cells was determined by analysis of the mitotic index (MI). The growth reaction was studied by linear growth indicators: the total length of the seedling, the length of the aerial part and roots, and the integral indicator of growth and biosynthetic processes – the accumulation of biomass. According to the results of the experiments, it was shown that the mitotic activity of root meristems under the influence of red light on the aerial part in seedlings of the LDP of pea Metsenat decreased slightly – by 8 %, and in the seedlings of the SDP of soybean Korsak increased significantly – by 47 %. The linear growth and accumulation of biomass in the aerial part under the action of RL irradiation in seedlings of pea of the Metsenat variety and soybean of the Korsak variety decreased, and this effect was more pronounced in soybean than in pea. During irradiation of RL the linear root growth and their biomass accumulation in seedlings of LDP pea decreased slightly, while at the same time, these processes in the roots of soybean SDP seedlings were significantly stimulated. Under the influence of RL in pea seedlings, the growth rate did not change in the length of the aerial part, but in the roots increased, while the rate of biomass accumulation by them decreased. In soybean seedlings during RL irradiation, the growth rate of both the aerial part and the roots decreased, the biomass accumulation rate by the aerial part increased, and by the roots – decreased. LDP of pea Metsenat and SDP of soybean Korsak variety differ in the nature of the reaction of growth processes in response to irradiation of RL. The activation of the phytochrome system in the aerial part causes changes in the proliferative activity and growth processes of the roots, which indicate a systemic response of the plant organism to the action of this factor. The relationship of the photoperiodic reaction of plants with the realization of phytochrome signal in the plant by activating or inhibiting the proliferative activity of root meristems and growth reactions is discussed.